Motivating Students to Perform Better Orally in a Communicative Language Teaching Framework - CHELBI, Rym Ghosn El-Bel (Journal of Human Sciences, 2011)
“Communicative Language Teaching” is a method used tomotivate the students to better oral performance. In this article,we have presented the characteristics of this method that wehave tested through a study realized in the department of ForeignLanguage at Mentouri University Constantine. The results thatwe have obtained after the signing of two questionnaires, oneaddressed to a sample of teachers and another to a sample ofsecond year L.M.D. students of English, demonstrated that themethod is motivating and helps students for a better oralperformance.